Por currículos crápulas: subversões a curricularização escolarda função-psi - Kuster, Patrick Stefenoni (2022)
In everyday school life, medical senses arise impregnating children in school relationships in which they become medical things, even if they are not, at first, sick. Thus, this Ph.D. work questions how a medical reality is attributed to them, when they are not sick, and how this might be taking place in schools. Through mnemonic records of what was said and done during apparently confusing school experiences emerges an efficient and precise medical-pedagogical engine. Designated by a function-psi, in the capillarity of its work, a power over life is enacted, that is, biopower. Our main theoretical-conceptual references are the works of Michel Foucault, Gilles Deleuze, Félix Guattari, and Fernand Deligny. The thesis aims to procedurally map the curricularization of function-psi in two municipal schools from Domingos Martins (Espírito Santo, Brazil). Recreating the direction of the microphysical mechanisms of power and focusing on their everyday operators and their subjectivation effects, amidst the curriculum practices, we propose the idea of an insidious medicalization that emerges, in different modulations, from the schools and how they increase their constitutive order. These maps found true school scoundrels through which, irreducible to the strategic meanings of this power over life, the command of these medical realities are subverted. In these intense experiences, some questions resonated: as contemporaries to this medicalization, what are we doing with ourselves and Education? Thus, this work in the field of curriculum intended to criticize the present by articulating emergency points of current power formations, affected by the dissidence lines risen by school scoundrels.